Importance of Windows of Exposure to Maternal High-Fat Diet and Feto-Placental Effects: Discrimination Between Pre-conception and Gestational Periods in a Rabbit Model - Rousseau-Ralliard, Delphine; Aubrière, Marie-Christine; Daniel, Nathalie; Dahirel, Michèle; Morin, Gwendoline; Prézelin, Audrey; Bertrand, Jérémy; Rey, Catherine; Chavatte-Palmer, Pascale; Couturier-Tarrade, Anne (Frontiers in Physiology, 2021)
Context and aim: Lipid over-nutrition in female rabbits, from pre-puberty, leads to impaired metabolism (dyslipidemia and increased adiposity) and follicular atresia and when continued during gestation, affects offspring phenotype with intrauterine growth retardation (IUGR), along with placental and lipid metabolism abnormalities. Growth retardation was already observed at embryo stage indicating a possible implication of periconceptional exposure. The objective of the present work was to discriminate the effects of preconception and gestational exposures on feto-placental development. Material and methods: Rabbit one-day zygotes were collected from female donors under control (C) or high-fat-high-cholesterol (H) diet and surgically transferred to the left and right uterus, respectively, of each H (n=6) or C (n=7) synchronized recipients. Close to term, 4 combinations of feto-placental units were collected: CC (n=10), CH (n=13), HC (n=13) and HH (n=6) for biometry analyzes. Fatty acid (FA) profiles were determined in placental labyrinth, decidua, fetal plasma and fetal liver by gas chromatography and further explored through principal component analyses (PCA). Candidate gene expression was also analyzed by RT-qPCR in placenta and fetal liver. Data were analyzed by Kruskal-Wallis followed by a Dunn’s pairwise comparison test. The combination of different data sets were combined and explored through multifactorial analyses (MFA). Results: Compared to controls, HH fetuses were hypotrophic with reduced placental efficiency and altered organogenesis, CH presented heavier placenta but less efficient, whereas HC presented a normal biometry. However, the MFA resulted in a good separation of the 4 groups, discriminating the effects of each period of exposure. HFHCD during gestation led to reduced gene expression (nutrient transport and metabolism) and big changes in FA profiles in both tissues with increased membrane linoleic acid, increased lipid storages and polyunsaturated-to-saturated FA ratios. Preconception exposure had major effect on fetal biometry and organogenesis in HH with specific changes in FA profiles (increased MUFA and decreased LCPUFA). Conclusion: Embryo origin left traces in end-gestation feto-placental unit, however maternal diet during gestation played a major role, either negative (HFHCD) or positive (control). Thus an H embryo developed favorably when transferred to a C recipient (HC) with normal biometry at term, despite disturbed altered FA profiles.